2022
DOI: 10.1371/journal.pone.0264505
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with female age at first marriage: An analysis using all waves of the Pakistan Demographic and Health Survey

Abstract: In conventional Muslim societies, fertility occurs within the marital union. Therefore, fertility outcomes depend on females’ age at first marriage (AFM). The present study explores the pattern of AFM in Pakistan, analyses of which are scarce in the literature. We aim to identify the factors associated with the AFM among currently married women in Pakistan. Demographic factors like birth cohort, and socioeconomic and cultural factors such as province and place of residence, education level, whether or not a wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
(34 reference statements)
0
7
0
1
Order By: Relevance
“…This is not a novel discovery in and of itself, as it has been noted that female education tends to delay the age of first marriage leading to a delay in age at first birth for females. In this regard, female secondary education had an even stronger association with delayed entry to marriage and parenthood than primary education [35,43,44]. A rather intriguing finding reported in this work was the fact that the postponement of reproductive role assumption was stronger among educated female youths living in urban areas than their rural counterpart.…”
Section: Education Appears To Affect the Sexual And Reproductive Beha...mentioning
confidence: 45%
“…This is not a novel discovery in and of itself, as it has been noted that female education tends to delay the age of first marriage leading to a delay in age at first birth for females. In this regard, female secondary education had an even stronger association with delayed entry to marriage and parenthood than primary education [35,43,44]. A rather intriguing finding reported in this work was the fact that the postponement of reproductive role assumption was stronger among educated female youths living in urban areas than their rural counterpart.…”
Section: Education Appears To Affect the Sexual And Reproductive Beha...mentioning
confidence: 45%
“…Female age at marriage are influenced by number of different factors both at family and societal level (Dixon, 1971) which varies due to many reasons. Female's education (Abalos, 2014;Islam et al, 2013), place of residence (Caltabiano & Castiglioni, 2008;Jayaraman et al, 2009;Kamal, 2011), religion (Pazvakawambwa et al, 2013), ethnicity (Misunas et al, 2021), birth cohort (Rasul et al, 2022), female's work status (Kamal, 2011;Rasul et al, 2022), family economic status (Aryal, 2007;Pazvakawambwa et al, 2013), husband education (Caltabiano & Castiglioni, 2008;Kamal, 2011), father's education (Aryal, 2007;Kamal, 2011), female's age at menarche (Aryal, 2007 ) and premarital sex (Misunas et al, 2021) have been observed as some of the significant determinants associated with female age at marriage. The role of female's education is shown to be one of the major influential factors to determine their marrying age, since staying in school till to the higher level of educational attainment is expected to get delayed marriage (Glick et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The age of marriage, both legally and culturally, varies from country to country, and there are many debates supporting marriage at an older age or a younger age [9]. Although most girls today marry at an older age, early marriage is still common in many countries like Pakistan [9], Bangladesh [10], Malawi [11], Ethiopia [12], and Hosseini and Asadisarvestani BMC Women's Health (2022) 22:542 Nepal [13]. Generally, this phenomenon occurs especially in developing countries and the regions where out-ofwedlock childbearing is not approved [9,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Although most girls today marry at an older age, early marriage is still common in many countries like Pakistan [9], Bangladesh [10], Malawi [11], Ethiopia [12], and Hosseini and Asadisarvestani BMC Women's Health (2022) 22:542 Nepal [13]. Generally, this phenomenon occurs especially in developing countries and the regions where out-ofwedlock childbearing is not approved [9,14,15]. In these regions, the age of the first marriage is influenced by a range of social, economic, and cultural factors (such as ethnicity and education level), especially in women [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation